Exploring Tax Strategies: Leverage and Firm Size Effect in Manufacturing Firms - Wafa, Khoerul; Ratiyah; Reptiningsih, Eni; Hartanti (Santoso Academy Network, 2024)
The purpose of this study is to examine how leverage and firm size affect tax evasion in manufacturing companies that are listed on the Indonesia Stock Exchange (IDX) between 2021 and 2023. The lawful use of tax laws to lower tax obligations is known as tax avoidance. This practice has a substantial impact on state revenue, particularly in Indonesia where tax receipts are rising but the tax ratio stays low. Secondary data from financial reports of industrial firms is used in this study. By calculating business size using the natural logarithm of total assets and assessing leverage using the debt-to-asset ratio (DAR), it applies quantitative research approaches. The research results show that leverage has a significant influence on tax avoidance, where firms with higher levels of debt tend to carry out more tax reduction strategies because of the tax deduction from interest expenses. In contrast, firm size does not show a significant effect on tax avoidance, indicating that both large and small firms adopt similar tax avoidance measures. Managerial implications These findings emphasize the importance of regulatory oversight of corporate leverage and considering firm size in designing tax policies aimed at minimizing tax avoidance practices.